2015
DOI: 10.2147/ijn.s82807
|View full text |Cite
|
Sign up to set email alerts
|

Effects of zinc oxide nanoparticles on Kupffer cell phagosomal motility, bacterial clearance, and liver function

Abstract: Background Zinc oxide engineered nanoparticles (ZnO ENPs) have potential as nanomedicines due to their inherent properties. Studies have described their pulmonary impact, but less is known about the consequences of ZnO ENP interactions with the liver. This study was designed to describe the effects of ZnO ENPs on the liver and Kupffer cells after intravenous (IV) administration. Materials and methods First, pharmacokinetic studies were conducted to determine the tissue … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 61 publications
(51 reference statements)
2
15
0
Order By: Relevance
“…Hexagonal lobules are centered on the central vein that exhibited moderate to severe congestion with the hepatic artery, sinusoids and Portal vein. These investigations are coinciding with Landsiedel et al, [25] and Watson et al, [26] who claimed that the histological analysis of liver sections showed areas of necrosis accompanied by significant inflammatory cell infiltration near the hepatic portal triad at day 7 of exposure. By this time, the engulfed ZnO ENPs would have dissolved, releasing zinc ions, which may have caused toxicity to the surrounding hepatocytes.…”
Section: Discussionsupporting
confidence: 80%
“…Hexagonal lobules are centered on the central vein that exhibited moderate to severe congestion with the hepatic artery, sinusoids and Portal vein. These investigations are coinciding with Landsiedel et al, [25] and Watson et al, [26] who claimed that the histological analysis of liver sections showed areas of necrosis accompanied by significant inflammatory cell infiltration near the hepatic portal triad at day 7 of exposure. By this time, the engulfed ZnO ENPs would have dissolved, releasing zinc ions, which may have caused toxicity to the surrounding hepatocytes.…”
Section: Discussionsupporting
confidence: 80%
“…The results indicate that administration of ZnO-NPs transiently inhibited Kupffer cell phagosomal motility and later induced hepatocyte injury. In addition, the data show that diminished Kupffer cell organelle motion correlated with ZnO-NPs-induced liver injury [62]. This effect would be important to justify the results obtained in our work.…”
Section: Tem Analysis Of Liver and Kidney Biopsiessupporting
confidence: 76%
“…It is possible that the free radicals generated by the ZnO-NPs [60] cause lipid peroxidation and oxidative stress, inducing steatosis in the liver of the mice, specifically in specimens given ZnO-NP doses, these mice being the ones which presented this disease. In addition, ZnO-NPs could be dissociated in biological media [61] [62]. Alterations in the hepatic ultrastructure in rats have also been reported for nanoparticles of ceria [63].…”
Section: Tem Analysis Of Liver and Kidney Biopsiesmentioning
confidence: 93%
See 1 more Smart Citation
“…Importantly, these results also differed greatly from the Fe 2 O 3 nanofiller or comparator material used in the nanocomposite synthesis, which showed no significant biological activity or toxicity in SAEC. We have shown in previous studies that raw iron oxide ENMs are thought to be biocompatible and inert, and hold minimal toxic potential (Watson et al , 2015), which suggests other mechanisms or properties may be influencing the observed toxicity of PE 5% Fe 2 O 3 LCPM exposures.…”
Section: 0 Discussionmentioning
confidence: 97%